2008
DOI: 10.1038/ja.2008.42
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Malformin C, an Inhibitor of Bleomycin-Induced G2 Arrest

Abstract: Total synthesis of a fungal cyclic peptide, malformin C, recently rediscovered as a G2 checkpoint inhibitor was completed. Our synthesis involved a convergent approach with respect to a linear pentapeptide, cyclization, and oxidative disulfide formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…1D and 2D-NMR spectra were measured on a Bruker ARX-300 spectrometer (300 MHz for 1 H, 75 MHz for 13 C). The pure compound was identified as malformin C via comparison of data with those previously reported [ 16 ].…”
Section: Methodsmentioning
confidence: 93%
“…1D and 2D-NMR spectra were measured on a Bruker ARX-300 spectrometer (300 MHz for 1 H, 75 MHz for 13 C). The pure compound was identified as malformin C via comparison of data with those previously reported [ 16 ].…”
Section: Methodsmentioning
confidence: 93%
“…Our study also demonstrated that MA1 treatment induced cell cycle arrest at the sub-G1 phase in human colorectal cancer cells. Previously, MA1 and Malformin C were found to abrogate bleomycin-induced G2 arrest, resulting in a drastic decrease in cells at the G2 phase and increase in cells in the sub-G1 phase (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Malformin A1 (MA1) is a bicyclic pentapeptide containing five amino acids: L-isoleucine, L-valine, D-leucine, and two D-cysteines (12). MA1 is the most well-studied out of the malformin subtypes, and its various biological activities have been reported previously, including causing malformations in plants, having some antibacterial effects (13)(14)(15), enhancing cellular fibrinolytic activity (16 -18), preventing IL-1-induced procoagulant reaction (19,20), and inhibiting the cell cycle at G2 checkpoint followed by DNA damage (21,22). Additionally, the anticancer activity of MA1 has been reported in various human cancer cells including colorectal cancer (9,22-24).…”
Section: Introductionmentioning
confidence: 99%
“…22 Since then, malformin A has been shown to possess antibiotic activity 23 and inhibit mitosis and the premitotic phase in animal cultures. 24,25 The eight-membered ring consisting of the atoms from the disulfide of the vicinal D-Cys residues is a particularly noteworthy feature of the malformins because the energetic barrier to cis/trans-isomerization of the D-Cys-D-Cys amide could be reduced by the eight-membered ring strain. Theoretical calculations, 26,27 IR studies, 28 and X-ray crystallography 29,30 of L-Cys-L-Cys disulfides suggest that the amide in the dipeptide is cis, but it was unknown if this is maintained in bicyclic systems such as the malformins.…”
Section: Malforminmentioning
confidence: 99%